The anatomy of sentiment-driven fluctuations - Sushant Acharya; Jess Benhabib; Zhen Huo (Bank of Canada, 2021)
We show that sentiments - self-fulfilling changes in beliefs that are orthogonal to fundamentals - can drive persistent aggregate fluctuations under rational expectations in a beauty contest game. Such fluctuations can occur even in the absence of exogenous aggregate fundamental shocks. Moreover, sentiments alter the volatility and persistence of aggregate outcomes in response to fundamental shocks. We provide (i) necessary conditions under which sentiments can affect aggregate outcomes in equilibrium and (ii) conditions under which sentiments drive persistent fluctuations and when they only affect aggregate outcomes contemporaneously. We also show that sentiment equilibria are stable under least-squares learning while the fundamental equilibrium is not.
Keywords: E20; E32; F4; 330; Business fluctuations and cycles; Economic models